2022
DOI: 10.1002/ppul.25974
|View full text |Cite
|
Sign up to set email alerts
|

Indications and outcome of home high‐flow nasal therapy in children, a single‐center experience

Abstract: High‐flow nasal therapy (HFNT) is a safe and simple way to deliver humidified air and oxygen for respiratory support in infants and children. HFNT is well established in an inpatient setting, but home HFNT lacks evidence. In the current study, we studied characteristics and outcomes of pediatric patients with home HFNT. In a monocentric retrospective analysis of data for 10 years (April 2010–April 2020), patient characteristics from the time point of the first discharge from hospital with home HFNT‐treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In one small case series, 12/17 (71%) patients with BPD discharged using HFNC were able to successfully wean to room air after an average of about 6 months. However, 4/17 (24%) of these patients died prior to weaning from support, which is much higher than demonstrated in other cohorts of patients with severe BPD (89,90). Because of the high rates of mortality following discharge, home HFNC should be considered with extreme…”
Section: Weaning Non-invasive Supportmentioning
confidence: 88%
“…In one small case series, 12/17 (71%) patients with BPD discharged using HFNC were able to successfully wean to room air after an average of about 6 months. However, 4/17 (24%) of these patients died prior to weaning from support, which is much higher than demonstrated in other cohorts of patients with severe BPD (89,90). Because of the high rates of mortality following discharge, home HFNC should be considered with extreme…”
Section: Weaning Non-invasive Supportmentioning
confidence: 88%
“…Therefore, there have only been a few clinical reports of home HFNC implementation [ 1 , 2 ], which is why we included a device with both nCPAP and HFNC settings. To our knowledge, only one study has reported home HFNC use in cases of BPD [ 6 ]. However, while that report described several cases of BPD with a home HFNC, salient details, such as the clinical course of the patients, indications for use, and issues with home HFNC use, were lacking.…”
Section: Discussionmentioning
confidence: 99%